2012
DOI: 10.1371/journal.pone.0043129
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Farmed Escapees in the Wild: A Spatio-Temporal Analysis of Atlantic Salmon Population Genetic Structure throughout Norway

Abstract: Each year, hundreds of thousands of domesticated farmed Atlantic salmon escape into the wild. In Norway, which is the world’s largest commercial producer, many native Atlantic salmon populations have experienced large numbers of escapees on the spawning grounds for the past 15–30 years. In order to study the potential genetic impact, we conducted a spatio-temporal analysis of 3049 fish from 21 populations throughout Norway, sampled in the period 1970–2010. Based upon the analysis of 22 microsatellites, individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
228
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(243 citation statements)
references
References 118 publications
(134 reference statements)
12
228
1
1
Order By: Relevance
“…Larger, more aggressive farm and hybrid fish may also displace native fish or force them into suboptimal habitats, which increases average mortality (McGinnity et al, 1997(McGinnity et al, , 2003Fleming et al, 2000). These studies suggest that repeated introductions of farm fish may depress the productivity of wild populations through both ecological and genetic mechanisms, in addition to fostering genetic homogenisation (Skaala et al, 2006;Glover et al, 2012) and potential loss of local adaptations. Most studies of the effects of artificial immigration of non-native fish (whether from farms or hatcheries), however, tend to emphasise group-level performance differences and typically overlook familylevel variation in performance (but see Skaala et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Larger, more aggressive farm and hybrid fish may also displace native fish or force them into suboptimal habitats, which increases average mortality (McGinnity et al, 1997(McGinnity et al, , 2003Fleming et al, 2000). These studies suggest that repeated introductions of farm fish may depress the productivity of wild populations through both ecological and genetic mechanisms, in addition to fostering genetic homogenisation (Skaala et al, 2006;Glover et al, 2012) and potential loss of local adaptations. Most studies of the effects of artificial immigration of non-native fish (whether from farms or hatcheries), however, tend to emphasise group-level performance differences and typically overlook familylevel variation in performance (but see Skaala et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Many wild Atlantic salmon stocks are currently severely depleted (ICES, 2010) and in some regions farm escapees can account for a third or more of salmon caught at sea (Hansen et al, 1999) or on the spawning grounds (Fiske et al, 2006). A range of studies have demonstrated that escaped farm salmon can successfully spawn in the wild (Fleming et al, 1996) and hence may contribute one-way gene flow from farm to wild gene pools (Clifford et al, 1998;Skaala et al, 2006;Glover et al, 2012Glover et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In a larger follow-up study with 21 salmon populations along the Norwegian coast, Glover et al (2012) found significant genetic changes in 6 populations, particularly in the River Opo, where most of the individuals now fail to assign to the DNA profile of the historic population. However, in spite of a high abundance of escaped farmed salmon for a number of years in River Etneelva, DNA microsatellites and DNA SNP marker studies suggest that so far there have only been small changes in the DNA profile of this population (Skaala et al 2006;Glover et al 2012).…”
Section: Major Population Threatsmentioning
confidence: 96%
“…However, developments in statistical analysis, molecular techniques and genomic tools mean that DNA-SNP and/or microsatellite markers distributed across the genome can now be analysed. Various assignment tests (Anderson & Thompson 2002;Falush et al 2003) can subsequently be used to classify individuals as wild, farmed or F1 hybrids (Vähä & Primmer 2006;Hansen & Mensberg 2009;Glover et al 2010Glover et al , 2012Karlsson et al 2011). Thus, farmed and F1 hybrids can subsequently be eliminated from spawning populations or from brood stock for the gene banks.…”
Section: Rehabilitation Of Freshwater Habitatsmentioning
confidence: 99%
“…Following the decline of wild stocks and growing local demand for these species in the seafood market, kob farming has been initiated in the emerging South African aquaculture sector (DAFF, 2012). Although this may relieve some pressure from the harvesting of wild stocks, it also poses some concerns due to the potential negative effects of interactions between wild and farmed fish, as it has been increasingly evident in other species (Bekkevold et al, 2006;Glover et al, 2012). The monitoring and evaluation of such interactions can, however, be challenging and depend on accurate understanding of intra-and interspecific boundaries (here intended as barriers to gene flow) (e.g.…”
Section: Introductionmentioning
confidence: 99%